Multi phenomena melt pool sensor data fusion for enhanced process monitoring of laser powder bed fusion additive manufacturing. (September 2022) - Gaikwad, Aniruddha; Williams, Richard J.; de Winton, Harry; Bevans, Benjamin D.; Smoqi, Ziyad; Rao, Prahalada; Hooper, Paul A.
Graphical abstract: Highlights: Laser spot size was varied to create flaws (porosity) in laser powder bed fusion (LPBF). Implementation of a multi-phenomena sensing system to capture (image) melt pool shape, size, spatter, and temperature distribution. Physical intuitive melt pool characteristics, were extracted and merged (sensor fusion ). Meltpool characteristics were used in computationally lightweight, simple machine learning models to predict type and severity of porosity. Proposed framework yields both high true positive (> 90%) and low false positive (< 1%) detection rates at par with complex deep learning models. Abstract: Finding actionable trends in laser-based metal additive manufacturing process monitoring data is challenging owing to the diversity and complexity of the underlying physical interactions. A single monitoring solution that captures a particular process phenomenon, such as a photodiode that tracks melt pool intensity, is not alone capable of evaluating process stability or detecting flaw formation with sufficient precision for routine application in industry. In this work, to improve flaw detection performance, we adopted a data fusion approach that captures multiple process phenomena. To demonstrate this, we acquired data from laser powder bed fusion (LPBF) builds of cylindrical specimens produced with different laser spot sizes, emulating defocusing due to process faults such as thermal lensing. The resulting specimens had porosity of varying types and severity, quantified by post-build non-destructive X-ray computed tomography, Archimedes density measurements, and destructive metallographic characterization. During the build, the melt pool state was monitored with two coaxial high-speed video cameras and a temperature field imaging system. Physically intuitive low-level melt pool signatures, such as melt pool temperature, shape and size, and spatter intensity were extracted from this high-dimensional, image-based sensor data. These process signatures were subsequently used as input features in relatively simple machine learning models, such as a support vector machine, which were trained to detect laser defocusing, and in addition, predict porosity type and severity. The results show that the data fusion approach significantly enhanced system performance by reducing the overall false positive rate from ∼ 0.1 to ∼ 0.001 without sacrificing the true positive rate (∼0.90). These results were at par with a black-box, deep machine learning approach (convolutional neural network).